An Investigation On Ceo Remuneration Versus Firm Financial Performance On Maximizing Shareholders Value In An Emerging Economic Market: Evidence From Public Listed Companies In Bursa Malaysia - Tan, Boon Twee (2021)
This study examines the relationship between CEO Remuneration and Company Performance of 130 Public Listed Companies in Bursa Malaysia for the year of 2019, after the introduction and adoption of Malaysia Code on Comorate Governance 2017 ("MCCG 2017"). The study employed both the Accounting Based Method (by using EBITDA and EPS) and market related based method (by using P/E Ratio and TSR) across all the 13 Business Sectors (since 24/09/2018) of Companies Listed in the Main Board of Bursa Malaysia by the Criteria of selecting the Top 10 Market Capitalisation Companies from each of the business sector respectively. The main objectives of the study are to examine the relationship between CEO Remuneration in Malaysia versus Company Performance in maximising shareholders' value and minimising the Agency Conflict in particular with regards to EBITDA, EPS, P/E Ratio and TSR post MCCG 2017. The secondly objectives ofthe study are to determine the effect of Firm Size, Company Financial Leverage and Liquidity (acting as Control variables/Moderator) in relation to Company Performance and CEO Remuneration. Our study found that there is a significant relationship between CEO Remuneration and Company Performance in term of EBITDA and EPS (both Accounting Based Method) and Firm Size have a significant relationship with Company Performance in term of EBITDA. However, the study also indicated to us that there is an insignificant relationship between CEO Remuneration and Company Performance in term P/E Ratio and TSR (both Market Related Based Method) in Malaysia. Furthermore, our study confirms and consistent with the finding of previous study that Company Financial Leverage have a negative relationship and impact on Company performance in term of EBITDA, EPS and P/E Ratio. Notwithstanding that, the study has shown to us Company Financial Leverage have a positive relationship with TSR. Nevertheless, Liquidity in term Of CutTent Ratio is found to be inqignificant to Company Performance in term of EBITDA, EPS, P/E Ratio and TSR. In addition, this study indicates to us that the Agency Problem or Conflicts could be minimise by tying CEO Remuneration with Company performance consistent With the Pay to Performance Framework in order to align the Top Management interest with Shareholders', interest and to create a ewin-win' situation for both besides maximising Shareholder's value and wealth. Finally, the Resender has observed that changes introduce by MACC 2017 especially in respect to Transparency, Disclosure of Top Management Remuneration, Linkage between CEO Remuneration and Company Performance has been followed by most of the public Listed Companies in Bursa Malaysia. Adherence to these best practices in MCCG 2017 is align with the Shareholders' interest and has greatly enhance the shareholders' value and wealth in Malaysia.